Nanotechnology and sociopolitical modernity in developing countries; case study of Iran - Ghazinoory, Sepehr; Ghazinouri, Reza (Technological and Economic Development of Economy, 2009)
What we must keep in mind is that although nanotechnology is an emerging and high technology, it is still technology or, in other words, it has an instrumental nature and in order to study its effect on societies we have to consider the role of instruments’ evolution in societies and study nanotechnology as the most recent part of this trend. In this article we study the nature of modern technologies, role of technology based economy on different social and political aspects of developing countries; we have a review on the concept of social and political modernity and describe how development of nanotechnology will accelerate those countries’ modernization from social and political point of view in addition to modernizing their economy. So this paper is a cross‐disciplinary study between nanotechnology and social sciences. There are two different scenarios about the future of nanotechnology. One is the proof of radical nanotechnology and the other is the acceptance of the claim that nanotechnology is only an enabling technology. In the present paper, we studied the effects of both scenarios. The obstacles to modernity in Iran and potential effect of nanotechnology on them are studied as a case study.Nanotechnologija ir besivystančių šalių socialinis ir politinis šiuolaikiškumas: Irano atvejisSantrauka. Nors nanotechnologija yra nauja ir pažangi technologija, ji tėra tik instrumentas. Norint įvertinti josreikšmę visuomenei, reikia išnagrinėti panašių instrumentų raidą visuomenėse ir vertinti nanotechnologiją kaip naujausią tendenciją. Šiame straipsnyje ištirta šiuolaikinių technologijų prigimtis, technologijos vaidmuo žinių ekonomikoje skirtingais besivystančių šalių socialiniais ir politiniais periodais, apžvelgtos socialinio ir politinio šiuolaikiškumo sąvokos, apibūdinta, kaip išsivysčiusios nanotechnologijos pagreitins šalių modernizaciją socialiniu ir politiniu požiūriu be jų ekonomikos modernizavimą. Šis straipsnis yra nanotechnologijos ir socialinių mokslų tarpdisciplininė studija. Yra du skirtingi nanotechnologijos ateities scenarijai: pirmasis teigia, kad nanotechnologija sukels radikalių pokyčių; antrasis skelbia, kad nanotechnologija yra tiktai galimybių suteikimo technologija. Šiame straipsnyje tyrinėti abiejų scenarijų padariniai, tirtos kliūtys šiuolaikiškumui Irane įsitvirtinti ir nanotechnologijos poveikis šaliai.Reikšminiai žodžiai: nanotechnologija, šiuolaikiškumas, Iranas, žinių ekonomika, prekinė priklausomybė, sociotechninė sistema, besivystančios šalys.First published online: 21 Oct 2010